Assessment of procrastination trait among dental students - A preliminary outlook - Sakshi Shukla; Manu Batra; Simarpreet Singh; Deeksha Gijwani; Thounaojam Leimaton; Parul Mangal (Wolters Kluwer Medknow Publications, 2020)
Background: Procrastination is a form of self-regulation failure characterized by the irrational delay of tasks despite potentially negative consequences. The scenario among dental students is virtually unknown. Aim: The aim was to evaluate the prevalence of trait procrastination among dental students. Materials and Methodology: A cross-sectional questionnaire-based survey was conducted during September 2019 which included BDS final-year students and interns for assessing their procrastination trait. Lay's Procrastination Scale (LPS)-student version was used to collect desired information. The descriptive statistics were computed to evaluate the prevalence of significant procrastination (LPS score ≥60), and inferential statistics was done using SPSS (v21.0 IBM) software. Results: The results showed that interns had significant procrastination prevalence (LPS score ≥60) as compared to BDS final-year students. The procrastination trait among males was found to be at higher extent as compared to females. Conclusion: Because procrastination has been consistently reported to exert an adverse influence on the academic performance of students, the final-year students, to obviate the downscaling in their performance, tend to have significantly lesser procrastination trait than the interns and these findings highlight the need for active measures to reduce the causes and consequences of procrastination in dental education.